Efektivitas Aromaterapi Lemon Suanggi terhadap Gejala Obstructive Sleep Apnea untuk Mencegah Penyulit Persalinan Kala I - Atikah, Sri; Rahim, Hindun; Kusumaningtyas, Febrianika Ayu; Wulansari, Meinita (Jurnal Ners, 2026)
Sleep-disordered breathing, particularly Obstructive Sleep Apnea (OSA), often goes undetected during pregnancy, especially in the third trimester. This condition may increase the risk of preeclampsia, prolonged labor, and fetal growth restriction due to reduced oxygen levels. This study aimed to evaluate the effectiveness of lemon suanggi (Citrus lemon L.) aromatherapy as a complementary therapy in reducing OSA symptoms among third-trimester pregnant women. The study employed a quasi-experimental design with a One Group Pre-test Post-test Design. Respondents were third-trimester pregnant women selected based on inclusion and exclusion criteria. Before the intervention, a pre-test was conducted to assess OSA symptoms using the STOP-BANG questionnaire and Epworth Sleepiness Scale (ESS), along with measurements of respiratory rate and blood pressure. The intervention involved lemon suanggi aromatherapy administered through inhalation using an electric diffuser. The essential oil, distilled from lemon peel, was verified as safe for pregnant women. Aromatherapy was administered with 3–5 drops in 100 ml of water for 30 minutes before bedtime each day for one week. Post-test measurements were conducted using the same instruments, and observations were made on labor complications during the first stage, such as the duration of the latent and active phases. Results showed a decrease in STOP-BANG and ESS scores after the intervention, along with improved sleep quality, lower respiratory rate and blood pressure, and reduced daytime sleepiness. These effects are likely attributed to active compounds such as limonene, β-pinene, and citral, which act on GABAA receptors to induce relaxation. Overall, lemon suanggi aromatherapy proved safe and effective in reducing OSA symptoms and improving sleep quality among third-trimester pregnant women. This finding highlights the potential of local natural products to support maternal health and aligns with the national development of herbal-based therapies.